Edge Computing and Quantum Computing to Find Statistics of Pandemic - Fadziso, Takudzwa (Engineering International, 2018)
Edge computing and quantum computing to find statistics of pandemic’ analysis the use of edge and quantum computing in tracking the events happening in the world to get the statistical analysis done to find pandemic causing factors and situations so that authorities can be notified so that a potential pandemic can be avoided in the near future. An edge computing system enables customer data to be processed at the edge of the network to as close as possible to the originating source. Quantum computing is an aspect of computer processing that concentrates on creating machines, computer systems, and technology using the tenets of quantum theory. The application of edge and quantum computing in the healthcare sector, just like in other industries, can enable significant advantages that only traditional computers may not bring.